1975
DOI: 10.1073/pnas.72.4.1635
|View full text |Cite
|
Sign up to set email alerts
|

Functional intermediates in reaction of cytochrome oxidase with oxygen.

Abstract: The development of a low temperature kinetic method for the flash photolysis of the compounds of membrane-bound cytochrome as with carbon monoxide in the presence of oxygen affords evidence for three categories of functional intermediate compounds of cytochrome a3 and oxygen. The three classes are identified as follows: Compounds of Type A are considered to be "oxy" compounds of the ferrous heme. They have the composition asQ-0,. Compounds of Type B are considered to be peroxide compounds (Cu2+ass+-02. or Cul+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
98
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 22 publications
6
98
0
Order By: Relevance
“…Discussion tic of the a3 form [10] we have demonstrated on the hand that the reaction with oxygen of mitochondrial cytochrome oxidase in the mixed valence state does not lead to the formation of the fully oxidized state. This result is consistent with the prominent absorbance increase observed at 606 nm [4,5,12] when Compound C forms which strongly supports a reduced state of the iron. These considerations have suggested 2 + the formulation of Compound C as a3 -0g -Cu 2+ 3+ [9].…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Discussion tic of the a3 form [10] we have demonstrated on the hand that the reaction with oxygen of mitochondrial cytochrome oxidase in the mixed valence state does not lead to the formation of the fully oxidized state. This result is consistent with the prominent absorbance increase observed at 606 nm [4,5,12] when Compound C forms which strongly supports a reduced state of the iron. These considerations have suggested 2 + the formulation of Compound C as a3 -0g -Cu 2+ 3+ [9].…”
Section: Resultssupporting
confidence: 79%
“…On the other hand we have shown that a3 forms before the complete disappearance of Compound A expressed by the absorbance decrease at 590 nm on fig.2. The results in fig.2 provide evidence that cytochrome c oxidation may occur at temperatures lower than -50°C previously suggested as a limit [5]. The oxidation of cytochrome c implies the one of cytochrome a to a certain extent.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Recently, there has been a great deal of interest in the chemical and physical properties of various inhibitor complexes of cytochrome c oxidase [3][4][5][6][7]. In particular, considerable effort has been spent on studying the cyanideand carbon monoxide-bound protein with the hope of trapping one or more of the metal components in the oxidized or reduced form [8][9][10][11]. The rationale for such studies is the possibility that 'mixed valence' forms of the CN-or CO-inhibited protein might provide some clues about the mechanistic pathway of electron transfer to oxygen as well as the interaction of the four metal components in the functional protein.…”
Section: Introductionmentioning
confidence: 99%